1998
DOI: 10.2307/3551727
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Status, Health Behaviours and Health: Implications for Social Assistance and Health Care Policy

Abstract: Cette étude a examiné les liens entre le statut de pauvreté, les comportements en matière de santé et la santé de 130 Albertains vivant au sein de familles pauvres. Pour les fins de cette étude, le statut de pauvreté indiquait si les familles pauvres recevaient de l'assistance sociale et profitaient de soins de santé complets gratuits ou plutôt si elles travaillaient sans avoir accès à des soins de santé gratuits. Les résultats de sept analyses différentes indiquent que le statut de pauvreté était relié de div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…Our findings reinforce the need identified in a previous study [78] for the federal and provincial/territorial governments to ensure the provision of comprehensive health benefits to all those with low incomes, including people employed in low paying jobs, people receiving employment insurance, and people receiving student loans. In this regard, assertions by some recent national health care reform commissions and some health policy experts about the importance of expanding the comprehensiveness of publicly funded health care services in Canada are encouraging.…”
Section: Increase Access To Health-related Servicessupporting
confidence: 91%
“…Our findings reinforce the need identified in a previous study [78] for the federal and provincial/territorial governments to ensure the provision of comprehensive health benefits to all those with low incomes, including people employed in low paying jobs, people receiving employment insurance, and people receiving student loans. In this regard, assertions by some recent national health care reform commissions and some health policy experts about the importance of expanding the comprehensiveness of publicly funded health care services in Canada are encouraging.…”
Section: Increase Access To Health-related Servicessupporting
confidence: 91%
“…18,19 Although most mothers in the group of children who underwent poisoning had higher educational level, there was no significant difference in comparison to mothers in the control group. Similar data were found in a study on Although most caregivers showed higher frequency for the variable "be aware of the toxic action of agents available in the home," parents of children who did not undergo poisoning were twice as likely to have greater knowledge, as well as the fact that the variable "caregiver distraction"…”
Section: Discussionmentioning
confidence: 95%
“…Do the working poor hold different attitudes toward injury and childcare, or do they lack the means or time to take their child to a physician for care? Williamson and Fast reported that social assistance recipients seek medical treatment more frequently than the working poor [25] and these differences could contribute to the higher rates of childhood injury seen in this study.…”
Section: Discussionmentioning
confidence: 96%